Political Governance and Citizen Rights - Muhammad, Tara Omar (Journal of Legal and Political Studies, 2022)
The concept of cultural pluralism is one of the important concepts in mod-ern society, which includes culturally diverse groups, which poses prob-lems about unity in the context of diversity and harmony in the context of respect for difference. Multiculturalism, as a term that is etymologically distinct from the adjective multicultural in a society that consists of diverse cultural groups, has gained wide popularity in many countries, and has be-come a major part of the government policy agenda in managing ethnic pluralism within national Politics. In this context, the emergence of the term has been strongly associated with a growing awareness of the unin-tended social and cultural consequences of large-scale migration. This frantic use of cultural pluralism, formulated by the Royal Canadian Com-mission in 1965, has widespread support, as its proponent endorsed it both as a progressive political order and as an official clause of faith, a term associated in principle with the values of equality, tolerance and openness to immigrants from ethnically disparate backgrounds. Its sup-porters believe that it guarantees all citizens that they retain their identi-ties and feel a good sense of belonging. Typically, cultural pluralism repre-sents a social doctrine that distinguishes itself as a positive alternative to the Politics of inclusion, committed to the policy of recognizing the rights of citizens and the cultural identities of ethnic minority groups, and in a more general way, and proving and recognizing the value of cultural diver-sity. On the other hand, critics of cultural pluralism believe that its recogni-tion encourages separatism and constitutes a threat to national unity and social cohesion.
Keywords: Political Governance; Citizen Rights; Cultural Pluralism; Society; Constitutes; Identity